Pengembangan Multimedia Interaktif Berbasis Powtoon pada Pembelajaran Pendidikan Pancasila di Kelas IV Sekolah Dasar - Anisa, Nur; Rahmatina, Rahmatina (TSAQOFAH, 2025)
This study is motivated by the limited development of innovative and engaging technology-based learning media, as well as the challenges teachers face in designing effective interactive tools to support the teaching and learning process. The objective of this research is to develop interactive multimedia based on Powtoon for Pendidikan Pancasila instruction in fourth-grade elementary school, and to validate its effectiveness, practicality, and content validity. The research employed the Research and Development (R&D) method using the ADDIE development model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The trial subjects consisted of 12 students from SDN 04 Muaro Paiti, while the main research subjects included 18 students each from SDN 02 and SDN 03 Muaro Paiti. Data were collected through validation questionnaires from content, language, and media experts, as well as practicality questionnaires from teachers and students. The results showed that the developed interactive multimedia achieved content validity of 92.5%, language validity of 87.5%, and media validity of 92.5%—all within the “highly valid” category. Practicality testing indicated scores of 95.83% from teachers and 91.59% from students, while effectiveness testing reached 87.87%, classified as “highly effective.” Therefore, the Powtoon-based interactive multimedia is deemed suitable and effective for use as a learning medium to enhance the quality of Pendidikan Pancasila instruction in fourth-grade elementary education.